Platinum-Based Therapy in Adenosquamous Pancreatic Cancer: Experience at Two Institutions - De Souza, Andre Luiz; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Adenosquamous carcinoma of the pancreas is a rare type of pancreatic cancer. Although its molecular biology profile has been shown to be similar to pancreatic ductal adenocarcinoma tumors, it has different prognostic features. There is no consensus or guidelines to treat this tumor differently from pancreatic adenocarcinoma, but therapies based on gemcitabine and platinum chemotherapeutics such as cisplatin and oxaliplatin have been used based on results of a few case reports. We discuss the Abstract #269 from the 2014 ASCO Gastrointestinal Cancers Symposium showing better outcomes from platinum-based therapy in this type of tumors. Triggered by this study, we also present our experience. Prospective studies to investigate the clinical outcomes from platinum-based therapy and the role of target therapies such as erlotinib are warranted. Image: Pancreatic carcinoma stained for Dpc4 suppressor gene